URBAN EXPANSION (DIS) ORDERLY AND ITS CLASHES SOCIOENVIRONMENTAL: THE CASE OF THE CITY OF HORIZONTE, STATE OF CEARA - Albuquerque, Emanuel Lindemberg Silva; Gomes, Daniel Dantas Moreira; Medeiros, Cleyber Nascimento de; Souza, Marcos José Nogueira de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The municipality of Horizonte, located in the Metropolitan Region of Fortaleza – MRF spent the last 26 years by intense changes in their spatial configuration and in its environmental conditions, in order to separate two horizons, but connected, that outlined before and after the logic of industrialization. Thus, aimed to evaluate the territorial municipality of Horizonte, from new methods of integration and systematization of data and information by analyzing environmental. In order to quantify the urban sprawl in the years 1987, 1996, 2000, 2006 and 2010, multitemporal analysis was performed from TM/Landsat-5. In this perspective, a research has addressed, yet, historical factors that justify the use of space, well as aspects of its socioeconomic, population and its implications for environmental sanitation.